2021
DOI: 10.1002/solr.202100327
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Fine Control of Se Flux for Improving Performances of Sb2Se3 Solar Cells Prepared by Vapor Transport Deposition

Abstract: Sb2Se3 possesses a quasi‐1D (Q1D) structure, which creates an anisotropic charge transporting behavior in which the carrier transport is very efficient along the Q1D direction, which is beneficial for solar cells as long as the absorber is properly aligned along the preferred orientation. However, Sb2Se3 is prone to form donor‐like defects, such as VSe, that are detrimental to the performance. Therefore, both growth of Sb2Se3 along the preferred orientations and the suppression of the formation of VSe are cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…One research direction is the orientation control of Sb 2 X 3 films. 13,14 Based on the understanding that Sb 2 X 3 are composed of one-dimensional (1D) [Sb 4 X 6 ] n ribbons which are held together by vdW forces, [15][16][17][18][19] it has been reported that higher PV efficiency could be achieved when the Sb 2 X 3 films are oriented more perpendicular to the substrate due to more efficient carrier transport along ribbons than between them. 20 Consequently, researchers have focused on tailoring the growth orientation of Sb 2 X 3 films in order to achieve high efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…One research direction is the orientation control of Sb 2 X 3 films. 13,14 Based on the understanding that Sb 2 X 3 are composed of one-dimensional (1D) [Sb 4 X 6 ] n ribbons which are held together by vdW forces, [15][16][17][18][19] it has been reported that higher PV efficiency could be achieved when the Sb 2 X 3 films are oriented more perpendicular to the substrate due to more efficient carrier transport along ribbons than between them. 20 Consequently, researchers have focused on tailoring the growth orientation of Sb 2 X 3 films in order to achieve high efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…The vapor transport deposition (VTD) process could be a preferential choice to fabricate antimony chalcogenide films with various band gaps in view of the gained achievements before. This process was first developed to produce superstrate CdS/Sb 2 Se 3 solar cells by Wen et al and obtained a certified PCE of 7.6% in 2018 . Subsequently, Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, it may be possible that the Se surplus is effectively incorporated into the Sb 2 Se 3 structure or else it accumulates at the front interface in the form of elemental Se, as has been suggested elsewhere. 67 69 Further research and supporting evidence for verification are required.…”
Section: Resultsmentioning
confidence: 99%